2021
DOI: 10.1002/pits.22517
|View full text |Cite
|
Sign up to set email alerts
|

Do subjective and objective resilience measures assess unique aspects and what is their relationship to adolescent well‐being?

Abstract: Measurement of resilience is important within schools to support student mental health and well‐being. Resilience is defined as the healthy integration, adaptation, and positive functioning over time in response to the experience of adversity and challenge. This study explored the relationship between a subjective and objective measure of resilience and the respective predictability of psychophysical well‐being measures. A sample of 282 Year 10 students completed a subjective resilience measure (Connor–Davidso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 94 publications
(126 reference statements)
0
5
0
Order By: Relevance
“…De la Fuente et al (2021) [22], who conducted their study on Spanish university students, focus on resilience, positivity, and coping strategies as predictors of engagement in the context of burnout in university students, making proposals for therapeutic intervention for prevention in different student profiles, considering the work on resilience fundamental to withstand experiences of change. Jardim et al (2021) [19], who studied Portuguese university students; and Sigley-Taylor et al (2021) [18], who focused on Australian university students, highlight the importance of defining resilience and its implications in students.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…De la Fuente et al (2021) [22], who conducted their study on Spanish university students, focus on resilience, positivity, and coping strategies as predictors of engagement in the context of burnout in university students, making proposals for therapeutic intervention for prevention in different student profiles, considering the work on resilience fundamental to withstand experiences of change. Jardim et al (2021) [19], who studied Portuguese university students; and Sigley-Taylor et al (2021) [18], who focused on Australian university students, highlight the importance of defining resilience and its implications in students.…”
Section: Discussionmentioning
confidence: 99%
“…In direct relation to stress, we highlight two concepts: resilience and burnout. The first concept, resilience, is defined as healthy integration and adaptation over time in response to adversity and challenges [18]. Some college students lack the necessary skills to cope positively with the crises inherent to the college stage [19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By embracing a subjective perspective on body fat, 1 we follow the lead of other streams of research that have demonstrated the significant influence of subjective assessments of personal characteristics (versus objective measures of those same conditions) for factors ranging from psychological to physical to social characteristics. For example, research has clearly demonstrated the importance of subjective assessments of one's wellbeing (Diener et al., 1999), resilience (Sigley‐Taylor et al., 2021), pain (Stewart et al., 2021), sleep disruption (Dhruva et al., 2012), social status (Anderson et al., 2012), individual power (Anderson & Berdahl, 2002), and socioeconomic status (Adler et al., 2000) in fully understanding these constructs and their effects.…”
Section: Introductionmentioning
confidence: 99%